O monstro adaptado: uma análise narrativa das adaptações de Frankenstein para quadrinhos - Rodrigues, Felipe Lima (2018)
The analisis of the narrative focus in the adaptations of Frankenstein (1818), from Mary Shelley, for the comics, presents itself as a unique oportunity to study this aspect of the comics. The literary work adopts the genre of epistolary romances, in other words, it is told from the narratorprotagonist’s letters to a charater who plays the role of a reader. On this context,anachronisms are developed, changes in the narrative order which are coherent with therythm and the development of the plot on the written text. These narrative resources are elaborated in different ways on the comics adaptations with modifications, alterations, additions and exclusions. Besides that, the comics count not only on the narrator, present in the literature, but also on the “shower” – that entity who chooses which images will be framed and presented to the reader. The observation of these aspects and also in the way they manifest themselves in different works which have the same source, the book, makes itself relevant for the deepening of the comprehension of the narrative capacities of comics, its peculiarities and limits. The phenomena is approached following the thought of Gerárd Genette, showed in Palimpsestes (1992), which approaches the different formats the texts keep relation among themselves, from Linda Hutcheon, portrayed on her book “Uma teoria da adaptação” (2011), which observes the adaptation as intersemiotic translation and Evolution mechanism and permanence of the narrative in the culture, and Yves Reuter, who develops the different aspects of narrative in his studies. The narrative analysis are conducted according to the concepts presented by Thierry Groensteen in “O Sistema dos Quadrinhos” (2015) and Comics and narration (2013), which points it as inseparable the conduction of the narration conduction and the management of the space. In the analysis of Frankenstein adaptations by Roche (1947), Ito (1998), Macdonald (2009), Viney (2009), Sierra (2009), Wagner (2012), Borges (2012), Mousse (2009) and Katz (2017), the narrative peculiarities of each one are studied, as well as their differences and similarities to Shelley's book. Besides, the changes in the narrative structure of Mousse's adaptation (2009) is object of intense analysis. Such approaches aim throw light to the adaptation phenomena, more and more present in our culture, on the view of the narrative analysis.